Analisis Penerapan Pajak Pertambahan Nilai - Putri Adilla; Fahmi Fadilla; Julianti, Windi; Beni Wahyu Ariyudi; Dwi Fiona Sari (Sekolah Tinggi Ilmu Ekonomi LPI Makasar, 2025)
This study aims to analyze the application of Value Added Tax (VAT) on CV.Autobest Used Cars a company that focuses on the sale and purchase of used motor vehicles. With the change in tax regulations in Indonesia, this study examines how CV.Autobest Used Cars applies VAT in sales and purchase transactions, the rates used, and the level of fulfillment of the company in calculating, paying, and reporting tax obligations. The method applied is qualitative descriptive, which involves collecting primary data through interviews with owners and managers, as well as documentation related to transactions and tax invoices. The results of the study show that CV.Autobest Used Cars systematically applies VAT in every transaction, with the rate used being 10%, although the official rate has changed to 11%. The process of calculating and reporting tax obligations is carried out by following the established procedures, including consultation with tax professionals. The study found that companies always pay and report their obligations on time, which reflects a commitment to tax compliance.